2010
DOI: 10.1080/13575270903529136
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Breastfeeding and Stimulation in the Home on Cognitive Development in One-year-old Infants

Abstract: Research on the effects of breastfeeding on child cognitive development has produced conflicting results, and many studies do not account for infant stimulation in the home. The aim of this study is to determine whether breastfeeding predicts enhanced cognitive development in one-year-old infants after controlling for the main socio-economic and environmental factors, including stimulation in the home. This cross-sectional observational study involved 137 infants and their mothers. Information on maternal soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Overall, based on the primary endpoint of cognitive function, there were 21 studies showing no association between IQ and breastfeeding,24 25 30–32 35 36 39 54 56 62 63 73 74 86 87 89 91 97 100 101 28 positive studies,9 15 21 27–29 37 38 42 48 51 57 59 61 64 68 71 72 75 79–82 85 90 94 95 98 18 initially positive studies that became negative after accounting for confounders,13 23 26 33 43–46 49 50 52 55 65 66 69 78 84 96 and 17 studies where the initial positive effect was diminished but remained statistically significant after accounting for confounders (table 2). 22 34 40 41 47 53 58 60 67 70 76 77 83 88 92 93 99…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, based on the primary endpoint of cognitive function, there were 21 studies showing no association between IQ and breastfeeding,24 25 30–32 35 36 39 54 56 62 63 73 74 86 87 89 91 97 100 101 28 positive studies,9 15 21 27–29 37 38 42 48 51 57 59 61 64 68 71 72 75 79–82 85 90 94 95 98 18 initially positive studies that became negative after accounting for confounders,13 23 26 33 43–46 49 50 52 55 65 66 69 78 84 96 and 17 studies where the initial positive effect was diminished but remained statistically significant after accounting for confounders (table 2). 22 34 40 41 47 53 58 60 67 70 76 77 83 88 92 93 99…”
Section: Resultsmentioning
confidence: 99%
“…22 24 35–37* 38 51 54 60 64* 69 70* 72* 73 74* 78* 86* 90* Childhood: Refs. 9 13 15 21 23 25–34 37* 40–43* 45–50 52 53 55–59 61–64* 65–68 70* 72* 74* 75–78* 79–82 84–86* 87–90* 91–101…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that confounding variables, including socioeconomic status and maternal cognitive ability, affect the choice to breastfeed and the positive effects found. Measuring the duration of EBF accurately is challenging because of factors related to definition, timing, and duration of recall [ 11 , 12 ], and many of the studies were limited by poor documentation of breastfeeding patterns [ 13 , 14 ]. Further limitations included small sample sizes [ 15 , 16 ] and predominantly Caucasian populations, with only one small study from Africa [ 16 ], which found no association with cognitive development but some advantages for child behaviour in breastfed infants.…”
Section: Introductionmentioning
confidence: 99%
“…Well-documented associations have been reported between breastfeeding and a host of improved outcomes for children, including cognitive function, motor skills, immunology, and mortality (e.g. Cunningham 1995;Duijts et al 2010;Sloan et al 2010;Oddy et al 2011). Moreover, breastmilk provides benefits even to children in developed countries in obesity, blood pressure, cholesterol, and cancer domains (Hoddinott et al 2008).…”
Section: Introductionmentioning
confidence: 99%